2018
DOI: 10.1002/ajhb.23197
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of immunoglobulin G and immunoglobulin M levels in the breast milk of mothers with exclusive breastfeeding compared to mothers with non‐exclusive breastfeeding during 6 months postpartum: The Jordanian cohort study

Abstract: Objectives The purpose of this study was to measure changes in the concentration of immunoglobulin G (IgG) and immunoglobulin M (IgM) in the mature breast milk of Jordanian mothers during the first 6 months after giving birth between exclusively breastfeeding (EBF) mothers and non‐exclusively breastfeeding (non‐EBF) mothers. Methods A longitudinal follow‐up design was used to measure changes in the concentration of IgG and IgM in the mothers' mature milk during the first 6 months after giving birth. Sixty‐nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
2
14
1
Order By: Relevance
“…Additionally, the latest reports of Goonatilleke et al (15) showed the gradual decrease in IgM concentration from the beginning of lactation until 6 months. Similar results were presented by Abuidhail et al (21), who showed that the IgM concentration in milk samples from the 1st month of lactation was significantly higher (103 ± 31 mg/L) than for the 4th and the 6th month of lactation (64 ± 25 and 48 ± 18 mg/L, respectively) (21). Moreover, the concentration of IgM from the 2nd to the 6th day of lactation was positively associated with overweight and obesity of the mother before pregnancy as well as with primiparity and negatively associated with smoking during pregnancy (22).…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, the latest reports of Goonatilleke et al (15) showed the gradual decrease in IgM concentration from the beginning of lactation until 6 months. Similar results were presented by Abuidhail et al (21), who showed that the IgM concentration in milk samples from the 1st month of lactation was significantly higher (103 ± 31 mg/L) than for the 4th and the 6th month of lactation (64 ± 25 and 48 ± 18 mg/L, respectively) (21). Moreover, the concentration of IgM from the 2nd to the 6th day of lactation was positively associated with overweight and obesity of the mother before pregnancy as well as with primiparity and negatively associated with smoking during pregnancy (22).…”
Section: Introductionsupporting
confidence: 92%
“…These values are consistent with that of about 20 mg/L given by Broadhurst et al (19) for the same lactation period and lower than that established by Koenig et al (20) for early colostrum of term (54 ± 37 mg/L) and preterm birth (very preterm, 76 ± 38 mg/L; moderately preterm, 47 ± 42 mg/L). On the other hand, the report of Abuidhail et al (21) showed that the IgG concentration in milk samples derived from the 1st month of lactation was significantly lower (103 ± 41 mg/L) than that for the 4th and 6th month of lactation (133 ± 49 and 145 ± 54 mg/L, respectively), although the values were higher than previously reported.…”
Section: Introductioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The titer of SARS-CoV-2 RBD-specific IgA (AUC/mg of IgA) was higher in the serum group than the human milk group. The concentrations of IgA, IgM, and IgG in human milk [6][7][8][26][27][28][29] and serum samples 5 were in the ranges found in previous studies. Some women had greater antibody levels in human milk or serum samples than other women.…”
Section: Discussionsupporting
confidence: 77%